Six weeks of conditioning exercise increases total, but not free testosterone in lifelong sedentary aging men. (3rd July 2015) - Hayes, Lawrence D.; Sculthorpe, Nicholas; Herbert, Peter; Baker, Julien S; Spagna, Roberto; Grace, Fergal M.
Abstract: Introduction : Advancing age is associated with a gradual decline in circulating androgens, and the putative role of exercise training on systemic androgens remains to be adequately defined. Methods : The present investigation examined the impact of 6 weeks of supervised exercise training on resting levels of systemic hormones in a cohort of lifelong sedentary men [SED ( n = 28), 62.5 ± 5.3 years], compared with a positive control group of age-matched lifelong exercisers [LE ( n = 20), 60.4 ± 4.7 years, >30 years training history]. Blood hormones were sampled pre- and post-intervention from an antecubital forearm vein and analysed using electrochemiluminescent immunoassay. Cardiorespiratory fitness ( ) was determined via indirect calorimetry during an incremental cycle test to volitional exhaustion. Results : Analysis of variance (ANOVA) revealed a lack of significant change in any parameter amongst LE, whilst SED experienced a significant exercise-induced improvement in cardiorespiratory fitness and total testosterone (all p < 0.05). Concurrent increases in sex hormone-binding globulin (SHBG; p < 0.05) resulted in a lack of change to either bioavailable or calculated free testosterone ( p > 0.05) amongst SED. Conclusions : Although resting levels of systemic total testosterone increased in response to 6 weeks of exercise training, increases in SHBG negated any potential relationship between calculated-free or bioavailable testosterone. These findings indicate that increases in bioavailable testosterone fraction are not required for cardiorespiratory fitness improvements in aging men.